Perbaikan Sistem Kerja Proses Pemasangan Ban Truk dengan Perancangan Peralatan Pendukung Menggunakan QFD dan REBA - Hery Hamdi Azwir (Jurnal Rekayasa Sistem Industri, 2021)
PT.X as one of the heavy equipment manufacturing company are producing mining and non-mining transportation product (e.g. Semi Side Tipper (SST) & Dolly). In producing those kinds of products that mostly using tires, there is a process area to do mounting truck tire. Based on interviews and direct observation results, there is a symptom of Cumulative Trauma Disorders (CTD), especially in the low back area. The low back pain experienced by the operators is caused by an awkward posture that resulted from Manual Material Handling (MMH) in this process. Lifting and holding the tire that is located on the floor with diameter 1.2m, height 0.3m, and weight 90 Kg also the reasons why the awkward posture appears during the mounting truck tire process. Using Rapid Entire Body Assessment (REBA), Nordic Questionnaire, and followed by the Quality Function Deployment (QFD) approach for product design are used to do the improvement for the process. In the end, these ergonomics issues are solved by developing material handling tools that can minimize the risk and symptoms of CTDs. It can be shown by initially REBA score is on level 11 (Very High Risk) to level 7 (Medium Risk) and for the Nordic result from 7 body parts that feel discomfort, now it just becomes 1 body parts feel discomfort.